Comparison of three types of full-body compression garments on throwing and repeat-sprint performance in cricket players. Issue 7 (6th March 2007) - Duffield, Rob; Portus, Marc
Abstract : Objective: To compare the effects of three types of full-body compression garments (Skins, Adidas and Under Armour) on repeat-sprint and throwing performance in cricket players. Methods: Following familiarisation, 10 male cricket players performed four randomised exercise sessions (3 garments and a control). Each session involved a 30 min repeat-sprint exercise protocol comprising 20 m sprints every minute, separated by submaximal exercise. Throwing tests included a pre-exercise and a postexercise maximal distance test and accuracy throwing tests. During each session, measures of heart rate, skin temperature, change in body mass, rate of perceived exertion and perceived muscle soreness were recorded. Capillary blood samples were analysed before and after exercise for lactate, pH, O2 saturation and O2 partial pressure, and 24 h after exercise for creatine kinase (CK). Ratings of perceived muscle soreness were also obtained 24 h after exercise. Results: No significant differences (p>0.05) were evident in repeat-sprint performance (10 m, 20 m time or total submaximal distance covered) or throwing performance (maximum distance or accuracy). No significant differences (p>0.05) were observed in heart rate, body mass change or blood measures during exercise. Significant differences (p<0.05) were observed by way of higher mean skin temperature, lower 24 h postexercise CK values and lower 24 h postexercise ratings of muscle soreness when wearing compression garments. Analysis between respective brands of compression garments revealed no statistical differences (p>0.05). Conclusions: No benefit was noted when wearing compression garments for repeat-sprint or throwing performance; however, the use of the garments as a recovery tool, when worn after exercise, may be beneficial to reduce postexercise trauma and perceived muscle soreness.